Recent developmentsÂ towards detection & diagnosisÂ for management ofÂ plant viruses - AVINASH MARWAL, S.M.PAUL KHURANA* and (Indian Phytopathology, 2016)
Plant viruses are catastrophic despite their small size. They pose threat to crops depending on the strains, variety, season, seed, vector etc. affecting quality/quantity, reducing yields & profits by 5 to 15%. To reduce losses, virus management is achieved by use of healthy seed production through serological/ molecular detection. Virus detection is getting more challenging with globalization of trade/seed movement. Conventionally detection of viruses was through symptoms, later by Immunospecific Electron Microscopy using Transmission Electron microscopy (TEM) which is now practically replaced by sero-detection and molecular recognition of the nucleic acid sequences. ELISA is most popular for last 35-40 yrs for seed certification, followed by PCR but LAMP, LFD etc are now getting popular being as sensitive as RT-PCR. Besides, immuno-capture-PCR (IC-PCR) has come up having advantages of both PCR and serology. Recently developed immuno-precipitation (IP-PCR) is helpful in identification and molecular characterization of many viruses. It is robust, highly specific and minimizes the problems of RNA extraction by combining the serological efficiency and advantages of PCR. Multiplex RT-PCR simultaneously identifying multiple viruses and their virulence- or resistance-specific sequences. The non-thermal methods, like HDA, RPA, NASBA, etc. have proved suitable for poorly resourced laboratories and on-site testing. Recombinant DNA approaches are now available for detection of a wide range of infections and determining spacio-temporal development of epidemics for high accuracy forecasting.